Using Digital Platform Approach to Reduce Salt Intake in a Sample of UAE Population: An Intervention Study - Jarrar, Amjad H.; Al Dhaheri, Ayesha S.; Lightowler, Helen; Cheikh Ismail, Leila; Al-Meqbaali, Fatima; Bataineh, Mo'ath F.; Alhefeiti, Aseilah; Albreiki, Maithah; Albadi, Nouf; Alkaabi, Salama; Thondre, Pariyarath S. (Frontiers in Public Health, 2022)
Background Non-communicable diseases (NCDs) are the leading causes of mortality globally, accounting for more deaths than all other causes combined. World Health Organization launched its initiative in 2013 to reduce the intake of salt, the number of countries that have national sodium reduction strategies reached to 89 countries in 2017. In 2020, a study conducted in UAE showed more than 65% of the population exceeded WHO recommendations for salt intake. This study aimed to measure effectiveness of using digital platform approach to deliver educational materials to facilitate salt reduction in a sample of UAE population. Methods A controlled parallel intervention study was conducted in 2020. A sample of 121 participants completed the study and fulfilled the inclusion criteria with female to male ratio of (0.95:1.05). Participants were distributed randomly into three groups Control group, WhatsApp group, and Electronic Brochures group. Educational materials were distributed among participants of WhatsApp and Electronic brochures groups for 6-weeks. 24-h urinary excretion for sodium, potassium and creatinine, were measured in addition to KAP questionnaire and physical activity on two occasions at baseline and endpoint after 10-weeks (6-weeks of educational intervention). Results Both intervention groups showed a reduction in sodium with 278 mg (p < 0.001) for WhatsApp group (n = 41) and 169 mg (p < 0.018) for Electronic brochures group (n = 41), while Control group didn't show any significant change. Moreover, the percentage of participants exceeding WHO recommendation of sodium intake was significantly reduced at the end of intervention, (p = 0.004). WhatsApp group was more efficient in the percentage of reduction of participants exceeding WHO recommendation compared with baseline, with p = 0.023. A significant reduction in the practice toward adding salt during cooking, use of table salt, adding salt before tasting the foods and use of chicken stocks for both intervention groups was noted with p < 0.05. Intervention groups showed a significant improvement (p < 0.001) in Food and Health related knowledge after 6-weeks of intervention. Conclusion The digital platform approach such as WhatsApp and Electronic Brochure were effective in salt reduction. This study proves that UAE population is ready to reduce salt intake with appropriate education materials and easy delivery approach.